Pengembangan Media Sosial dalam Upaya Meningkatkan Penjualan Brand Batik Lokal “Qabudayan” - Ubaidirrohman, Wildan; Febriana, Poppy; Rochmaniah, Ainur (Warta LPM, 2024)
"Qabudayan" is a micro, small, and medium-sized enterprise (MSME) located in Malang City, East Java. The primary focus of this business is online marketing and sales of ready-to-wear clothing with an emphasis on traditional batik fabric motifs. Currently, "Qabudayan" faces challenges such as a lack of attractive product photos, limited to a logo design, and digital mockups. Other constraints include unpreparedness in the sales system, marketing activities, and human resource management, hindering online sales efforts. The goal of this community service activity is to provide assistance to "Qabudayan" in developing social media through the provision of attractive product photos and the creation of quality marketing content on the Instagram platform. This is expected to enhance the effectiveness of online marketing and sales activities. The community service process is carried out in three stages. The first stage involves a situational analysis by conducting interviews with the "Qabudayan" brand to identify the challenges faced. The second stage includes program planning involving activities such as product photo shoots, assistance in creating Instagram social media content, and promotions. The third stage is the implementation of the planned program. The expected output of this community service activity is to assist "Qabudayan" in developing their Instagram social media, enabling them to create professional photo and video content. By showcasing traditional batik fabric motifs and engaging Instagram social media content, it is hoped that not only will "Qabudayan" attract potential consumers, but it will also support efforts to preserve batik culture in society.